Poghiraha Adhara (Perkelahian Kuda) pada Masyarakat Muna - La Ode Usman; Wa Ode Sifatu; Rahmat Sewa Suraya (LISANI: Jurnal Kelisanan, Sastra, dan Budaya, 2023)
The purpose of this study is (1) to find out or analyze how the Muna people's oral form towards horses in West Muna Regency (2) what is the meaning of horse fighting in the Muna community in West Muna Regency. The method used in this study is qualitative research. Data collection was carried out using observation techniques (observation) in-depth interviews and documentation. The technique of determining informants in this study was carried out purposively. Data analysis techniques are as follows: data collection, data reduction, data presentation and drawing conclusions. The results of this study indicate that (1) The oral form of the Muna people in Latugho Village in the Pogiraha Adhara Tradition (Horse Fighting) in West Muna Regency. (2) The meaning of horse fighting in the Muna community in West Muna Regency contains moral messages about the courage of a man to maintain his dignity if his property rights are violated by others. In preparation, we as horse handlers must also understand what horses must participate in the arena, because it is not only about the existence of horses but also a high self-esteem value of the horse handler himself. In horse fighting, there is a special technique in defeating the opponent's horse, and that is why before being shown in the arena, a horse trainer usually trains the parts of the horse that can quickly defeat its opponent, including training the back legs as support when facing, training the front legs to push and also injure until the most fatal part is using its mouth to bite its opponent, usually the parts of the body that make the opponent give up quickly are the neck and also the genitals of the opponent's horse.